Pembuatan media interaktif dengan menggunakan microsoft powerpoint - Sunggu, Meliyani Rohana Ompu (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Today's students are a generation that differs in character from the previous generation, thus requiring different learning methods. Presentation of material in an interesting and interactive way is one way to be able to attract the attention of students during teaching and learning activities. In this activity there is a process of knowledge transformation from the teacher to the students. This causes the need for appropriate learning media so that the knowledge transformation process can run smoothly. The purpose of this study was to develop Powerpoint-based interactive learning media as a support for learning in schools by looking for the effectiveness of interactive learning media created by researchers. This type of research uses research and development (R&D) methods and is developed using the ADDIE development model, namely Analysis, Design, Develop, Implement, and Evaluate.